Mechanisms of Lignin-Degrading Enzymes - Xiao, Jianlong; Zhang, Sitong; Chen, Guang (Protein and Peptide Letters, 2020)
Lignin is abundant in nature. It is a potentially valuable bioresource, but, because of its complex structure, it is difficult to degrade. However, enzymatic degradation of lignin is effective. Major lignin-degrading enzymes include laccases, lignin peroxidases, and manganese peroxidases. In this paper, the mechanisms of degradation of lignin by these three enzymes is reviewed, and synergy between them is discussed.
Keywords: laccase